2014
DOI: 10.14231/ag-2014-010
|View full text |Cite
|
Sign up to set email alerts
|

Cubic fourfolds containing a plane and a quintic del Pezzo surface

Abstract: We isolate a class of smooth rational cubic fourfolds X containing a plane whose associated quadric surface bundle does not have a rational section. This is equivalent to the nontriviality of the Brauer class β of the even Clifford algebra over the K3 surface S of degree 2 arising from X. Specifically, we show that in the moduli space of cubic fourfolds, the intersection of divisors C 8 ∩ C 14 has five irreducible components. In the component corresponding to the existence of a tangent conic, we prove that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…This question, which was the original motivation for the current work, is now central to a growing body of research into arithmetic aspects of the theory of derived categories, see . As an example, if S is a smooth projective surface, Hassett and Tschinkel [, Lemma 8] prove that the index of S can be recovered from sans-serifDnormalbfalse(Sfalse) as the greatest common divisor of the second Chern classes of objects.…”
Section: Introductionmentioning
confidence: 99%
“…This question, which was the original motivation for the current work, is now central to a growing body of research into arithmetic aspects of the theory of derived categories, see . As an example, if S is a smooth projective surface, Hassett and Tschinkel [, Lemma 8] prove that the index of S can be recovered from sans-serifDnormalbfalse(Sfalse) as the greatest common divisor of the second Chern classes of objects.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent results involving cubic fourfolds containing a plane that make use of the tool of quadric fibrations can be found in [3], [5], [11], [22], [23], [25] and [27].…”
Section: 2mentioning
confidence: 99%
“…A number of recent papers have explored smooth limits of Pfaffian cubic fourfolds more systematically. For analysis of the intersection between cubic fourfolds containing a plane and limits of the Pfaffian locus, see [ABBVA14]. Auel and Bolognese-Russo-Staglianò [BRS15] have shown that smooth limits of Pfaffian cubic fourfolds are always rational; [BRS15] includes a careful analysis of the topology of the Pfaffian locus in moduli.…”
Section: Cubic Fourfolds Containing a Quintic Del Pezzo Surfacementioning
confidence: 99%